In vivo bioactivities of food protein-derived peptides – a current review. (June 2021) - Daroit, Daniel Joner; Brandelli, Adriano
Highlights: Food-derived proteins as sources of biologically active peptides. In vitro enzymatic hydrolysis as a major strategy to release bioactive peptides. Bioinformatics tools as valuable approaches for bioactivities screening. Specific peptides increasingly demonstrated to exert in vivo bioactivities. Bioactive peptides from protein-rich byproducts are also focused. Abstract : A great diversity of biological activities has been attributed to peptides. Despite food proteins are essentially considered as sources of dietary amino acids, bioactive peptides can be released during gastrointestinal transit, food fermentation, food maturation, and through enzymatic bioprocessing in vitro . Specific bioactive peptide databases integrated with predictive proteolytic cleavage of proteins are valuable tools allowing a rapid in silico screening of the bioactive potential of dietary proteins. The range of bioactivities generated by hydrolysis of food proteins include antioxidant, antihypertensive, antidiabetic, immunomodulatory, anticancer, and opioid activities. Some of these bioactivities have been also confirmed in vivo, reinforcing their physiological relevance. This review presents a current perspective on the production and main biological activities of peptides derived from food proteins.